THE EFFECT OF SERVICE QUALITY AND PROMOTION MEDIATED BY CONSUMER SATISFACTION ON CUSTOMER LOYALTY AT CV. ANANDA LINK - Raehan Ananda; Muh Abdul Aziz; Muhammad Khairul Amal (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The increasingly tight competition in the service industry demands companies to be able to retain customers by increasing loyalty. Customer loyalty is not only influenced by service quality and promotion, but also by the level of customer satisfaction as a mediating factor. This study aims to analyze the effect of service quality and promotion on customer loyalty with customer satisfaction as a mediating variable at CV. Ananda Link Sukabumi. This study uses a quantitative approach with a causal design. Data were obtained by distributing questionnaires to 175 active customers of CV. Ananda Link selected using the Krejcie and Morgan technique. Data analysis was performed using Structural Equation Modeling (SEM) with the help of AMOS 26.00 software. The results showed that service quality has a positive and significant effect on customer satisfaction (estimate = 0.654; p < 0.001) and customer loyalty (estimate = 0.438; p < 0.001). Promotion also has a positive and significant effect on customer satisfaction (estimate = 0.231; p = 0.025) and customer loyalty (estimate = 0.271; p = 0.004). Furthermore, customer satisfaction has been shown to have a positive and significant effect on customer loyalty (estimate = 0.234; p = 0.012). These findings indicate that customer satisfaction acts as a partial mediating variable in the relationship between service quality and promotion on customer loyalty